Prevalence of SARS-CoV-2 in newborns born to SARS-CoV-2-positive mothers at 2 weeks of life - Jan, Sophia; Katz, Robert; Fagan, David; Santos, Telmo; Beachy, Joanna C.; Steinway, Caren; Chen, Jack; Tsouristakis, Alina; Mancenido, Briana; Leung, Christy; Moore, Emily; Wilson, Estelle; et al. (Frontiers in Pediatrics, 2024)
Introduction Limited evidence exists on management recommendations for neonates born to SARS-CoV-2-positive mothers. This study looked at transmission risk of neonates presenting for primary care in a large regional health system within New York during the early months of the COVID-19 pandemic. Methods This was a prospective, observational study of newborns born to SARS-CoV-2-positive mothers presenting at any of the 19 Northwell Health-Cohen Children's Medical Center primary care practices who underwent another oropharyngeal/nasopharyngeal swab for detection of SARS-CoV-2 by day of life (DOL) 14. Results Among 293 newborns born to SARS-CoV-2-positive mothers who were negative at birth, 222 were retested at DOL 14, corresponding to times with different predominant strains. Of these, seven tested positive but had no symptoms. Conclusion The overall low transmission rates and absence of symptomatic infection support the safety of direct breastfeeding after hospital discharge with appropriate hand and breast hygiene.